ANALISIS KELAYAKAN USAHA PENGGILINGAN PADI DI DESA LAKATAN KECAMATAN GALANG KABUPATEN TOLITOLI - Nur Hikmah; Juria (Jurnal Agrotech, 2019)
This study aims to determine the level of Feasibility of "Cahaya Ummul " Milling. Determination of the object and location of the study was intentionally determined. The results showed that the analysis of the payback period or the length of time the investment will be returned occurred in 9 years 3 months, NPV analysis or estimated future cash flows discounted at 14% with a total NPV of 232,480,306 > 0 (positive), Net B / C analysis is the value of the ratio between the number of positive net benefit PVs with the number of negative net benefit PVs obtained a value of 1.19> 1, and the IRR analysis of the efficient level of an investment of 21,016% with an interest rate of 14% when evaluating. So this business was declared worth the effort.